The development of sequential injection analysis coupled with lab-on-valve for copper determination - Tapparath Leelasattarathkul (2018)
A sequential injection analysis (SIA) using lab-on-valve with air segmentation and spectrophotometric detection was designed for copper(II) determination. It is based on the reaction of copper(II) and 2-carboxy-2′-hydroxy-5′-sulfoformazyl benzene (Zincon) in a weak alkaline solution between the air zones. Beer's Law was obeyed over the range of 0.1-2.0 mg L-1copper(II) with a correlation coefficient 0.9985 and a slope of 0.2893 absorbance unit/mg L-1. The relative standard deviation was 2.0% for a series of 10 measurements of 0.5 mg L-1copper(II) solution. The detection limit (3 S/N) and the limit of quantification (LOQ) were 0.05 and 0.17 mg L-1respectively. This method has been successfully applied to determination of copper(II) in wastewater with a sample throughput of 120 h-1. The method is superior to the batchwise method in that it provides fully automation, rapidity, less reagents and sample consumption with little waste generation. © 2006.